Mushroom: an emerging source for next generation meat analogues - Panda, Jibanjyoti; Nath, Pinku Chandra; Mishra, Awdhesh Kumar; Rustagi, Sarvesh; Nayak, Debasis; Blundell, Renald; Mohanta, Yugal Kishore (Frontiers in Nutrition, 2025)
BackgroundIn recent years, plant-based and alternative protein sources have garnered attention. Since they may resemble the texture, flavour, and nutritional profile of typical meat products, mushroom-based meat substitutes have received attention. However, scaling up production, cost-effectiveness, and nutritional requirements similar to animal-based meat products remain hurdles. Thus, understanding these dynamics is crucial to the global development and adoption of next-generation mushroom-based meat substitutes.Scope and approachThis review examined and synthesised the current mushroom-based meat analogue research, concentrating on their physicochemical, nutritional, and qualitative properties. Also, evaluated worldwide market viability, consumer acceptance, and development and adoption difficulties and potential for next-generation mushroom-based meat substitutes.Key findings and conclusionsDue to their fleshiness, mushrooms can replace beef in sausages, nuggets, and patties. Rising vegetarianism and health concerns require meat substitutes. Due to their easy cultivation, excellent nutritional value, low fat and calorie content, and steady growth, mushrooms can meet this demand. However, there are still numerous chances and challenges to improve sensory features (texture, taste, and flavour), optimise processing, assess consumer satisfaction, and use different medicinal mushrooms as meat replacements. Thus, they are essential to the creation of nutritious, sustainable meat-based foods.